Synthesis and Binding of 3-Aminopyridine Derivatives at Central Nicotinic Receptors - Balboni, Gianfranco; Marastoni, Mauro; Merighi, Stefania; Borea, Pier Andrea; Tomatis, Roberto (Arzneimittelforschung, 2000)
A series of secondary and tertiary pyridyl amides as potential central nicotinic acetylcholine receptors (nAChRs) ligands were prepared. Amides displayed negligible or very low affinity, whereas two amines achieved by reduction of corresponding secondary amides, showed affinity in the nanomolar range for nAChRs.
Keywords: 3-Aminopyridine derivatives, receptor binding, synthesis; Nicotinic receptors ligands, central